2013
DOI: 10.1080/02786826.2013.823641
|View full text |Cite
|
Sign up to set email alerts
|

Study of Secondary Deposits in Multiple Round Nozzle Impactors

Abstract: Inertial impactors are devices that consist of one or more particle-laden jets impinging onto a surface. Many modern impactors consist of impaction stages that have hundreds of closely spaced jets that, under certain conditions, can influence each other. The objectives of this study were to experimentally quantify the effect of jet interactions on particle collection efficiency, and to determine the underlying collection mechanism. From this testing, three types of secondary deposits were found, defined as mid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…From the SEM images (SI Appendix, Fig. S4), it can be seen that the spots are slightly larger than the orifice diameter (0.2 mm), as expected (45). For dry Na 2 SO 4 (solid particles), no material collects in the center of the crystal where the particles initially impact.…”
Section: Significancementioning
confidence: 75%
See 1 more Smart Citation
“…From the SEM images (SI Appendix, Fig. S4), it can be seen that the spots are slightly larger than the orifice diameter (0.2 mm), as expected (45). For dry Na 2 SO 4 (solid particles), no material collects in the center of the crystal where the particles initially impact.…”
Section: Significancementioning
confidence: 75%
“…2B), there is a cloud resulting from bounce and capture as well as a significant amount of material near the centerline; however, 600-nm CML spheres do not form spots at the original impaction site but, rather, at the midlines. In this case, flow stagnation resulting from interactions from adjacent orifices increases impaction (45). A recent study that used flow fields and particle trajectory calculations, along with experimental studies of the impaction patterns formed by supermicron liquid oleic acid particles in a dual orifice test impactor (45), showed similar spots and midline patterns.…”
Section: Significancementioning
confidence: 80%
“…However, it should be noted that none of the above studies reveal a clear separation between particle deposition locations based on size, showing only a gradual shift in the radial extent of a Gaussian pattern. In addition to the deposition patterns discussed above, secondary deposits, or "halos", have been occasionally observed ringing the main deposit on an impactor stage (Berner 1978;Roeber 1957;Rocklage et al 2013;Oodo et al 1981). The particles in these "halo" deposits have diameters smaller than d 50 for the impaction stage, suggesting some relationship between deposition location and particle diameter, at least for particles smaller than d 50 .…”
Section: Discussionmentioning
confidence: 89%
“…The deposition patterns on impactor plates for traditional impactors have been previously investigated and described in the literature. These investigations have found that for typical operating conditions, the deposition pattern of a polydisperse aerosol is nominally a Gaussian distribution centered on the nozzle axis (Rocklage et al 2013;Roeber 1957;Berner 1978;Sethi and John 1993;John et al 1991). These studies did not, however, investigate the size distributions within the particle deposits.…”
Section: Discussionmentioning
confidence: 99%
“…Particles of that size range are often deposited via diffusion and could have deposited on the impactor nozzle/collection sections. Rocklage, Marple, and Olson (2013) have also identified multiple secondary deposited locations for round nozzle impactors. There was evidence of diffusion for particles 100 nm or smaller by increased collection efficiency.…”
Section: Discussionmentioning
confidence: 99%